Time trends, collaterals and cerebral autoregulation efficacy in acute ischemic stroke - Nuno Ricardo Sousa Gonçalves (2021)
Background and purposes: Cerebral autoregulation (CA) is crucial for stable blood perfusion pressure and is challenged during acute ischemic stroke. CA's efficacy and collateral arteries may play a key role in penumbral region perfusion during acute phase of ischemia. We aimed to investigate CA parameters in collateral arteries over the first 48 hours post-stroke and compare them between cerebral hemispheres. Methods: We enrolled 46 patients with acute ischemic stroke of the middle cerebral artery territory and monitored cerebral blood flow velocity (CBFV) of the main cerebral arteries with transcranial Doppler. We assessed dynamic CA by projection pursuit regression (PPR) from the spontaneous oscillations of blood pressure and CBFV from within 6 hours until 48 hours of symptom onset. Results: No differences were detected throughout time. Affected middle cerebral artery showed steeper autoregulatory gain (worse dynamic CA) than its contralateral after 48 hours of onset (0.42±0.37 vs 0.37±0.30 cm/s/mmHg, p<0.05). Slight asymmetries were found in CA mostly outside autoregulatory regions. Conclusion: Our findings advance on the knowledge of global CA impairment during acute phase of stroke. Understanding collateral arteries role and physiological mechanisms regarding their CA efficacy can be useful to personalize stroke hemodynamic management and predict stroke clinical outcomes.